Linking drug and food addiction: an overview of the shared neural circuits and behavioral phenotype - Passeri, Alice; Municchi, Diana; Cavalieri, Giulia; Babicola, Lucy; Ventura, Rossella; Di Segni, Matteo (Frontiers in Behavioral Neuroscience, 2023)
Despite a lack of agreement on its definition and inclusion as a specific diagnosable disturbance, the food addiction construct is supported by several neurobiological and behavioral clinical and preclinical findings. Recognizing food addiction is critical to understanding how and why it manifests. In this overview, we focused on those as follows: 1. the hyperpalatable food effects in food addiction development; 2. specific brain regions involved in both food and drug addiction; and 3. animal models highlighting commonalities between substance use disorders and food addiction. Although results collected through animal studies emerged from protocols differing in several ways, they clearly highlight commonalities in behavioral manifestations and neurobiological alterations between substance use disorders and food addiction characteristics. To develop improved food addiction models, this heterogeneity should be acknowledged and embraced so that research can systematically investigate the role of specific variables in the development of the different behavioral features of addiction-like behavior in preclinical models.